Implementation of the Islamic Religious Education Curriculum in Shaping Multicultural Social Cohesion Among Students - Al Musanna, Al Musanna; Abdussyukur, Abdussyukur; Bahri, Syamsul (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aims to examine the implementation of the Islamic Religious Education (PAI) curriculum in shaping students' social cohesion at SMA Negeri 1 Takengon, Central Aceh Regency. It employs a qualitative approach through field study methods. Qualitative data—namely the activities related to PAI curriculum implementation at SMA Negeri 1 Takengon—were obtained via in-depth interviews with the school principal, PAI teachers, and students, as well as through observation and documentation. Data were analyzed inductively through reduction, data display, and drawing conclusions. The results reveal that the implementation of the PAI curriculum at SMA Negeri 1 Takengon has been effective in fostering students’ social awareness. PAI teachers play an active role not only in delivering instructional content but also in exemplifying and guiding students to live harmoniously amidst diversity. The internalization of social cohesion values is carried out through discussion methods, case studies, and experiential learning. The study concludes that the PAI curriculum contributes significantly to forming students' social cohesion when supported by appropriate teaching strategies and a conducive school environment. Strengthening teacher capacities and integrating multicultural values into the curriculum are necessary to make religious education a primary pillar in maintaining national social integrity.